Presidenta Ereni Oliveira de Miranda: uma análise de sua gestão frente à Igreja Pentecostal Deus é Amor no período 2015-2022 - Camacho, Alberto de Lima (2022)
The research analyzes the trajectory of the current leadership of the Pentecostal Church God is Love, having as president Ereni Oliveira de Miranda, whose management begins in 2015. Because of that, the clipping is from the year 2015 to 2022. The research aims to present the process of transition and consolidation of the government of Ereni Oliveira de Miranda in the Pentecostal Church God is Love (PCGL). To do so, we seek to situate women in the context of Brazilian Pentecostalism, observing their performance in the PCGL. We present the management model of the PCGL under the government of David Miranda and the secondary place of Ereni Miranda in the decision-making processes of the institution and demonstrate the changes that took place in the management of PCGL under the presidency of Ereni Miranda and its importance to the women of the church. The methodology used was bibliographic and documental research. The research problem questions whether the Pentecostal Church God is Love presided over by a woman represents changes in the institution's management model. Other questions that derive from this are: How is the participation of women in the context of Brazilian Pentecostalism characterized and its importance for the Pentecostal Church God is Love? What was Ereni's role in the IPDA under the government of David Miranda? What impacts and changes have occured to other women in PCGL after Ereni Miranda's ascension to the presidency of the church? The results obtained demonstrate that there is an ongoing construction of leadership under Ereni's management. Even so, there is complexity in relation to this one, because it is an object in movement and that presents the researcher in Sciences of Religion with countless possibilities to explore it, whether from the gender perspective, power relations and the clash among leaders of the institution itself, the generational shock and gentrification of PCGL, and mediatization processes of society that generate other forms of religiosity.(AU)